Management of Treatment and Complications in Cancer Patients Admitted to Algology Outpatient Clinic: A Retrospective Evaluation (Annals of Medical Research, 2021)
Aim: In thist retrospective study, we evaluated pain intensity, pharmalogical therapy, patient satisfaction and rising complications of 241 oncology patients that applied to Department of Algology outpatient clinic at Inonu University Medicine Faculty, between January 2011 and March 2012.
Keywords: s: Cancer Pain; Pain Management; Complication.